Adaptive Dynamic Inverse Controller for Advanced Coupled Tank Liquid Levels System - Abdalla, Ahmed N.; Keream, Settar S.; Ibrahim, Thamir K.; Tao, Hai (2016)
Inversion technique has been successfully applied in the tracking control of many Multi Input Multi Output (MIMO) process of engineering as well as science. The difficulty in controller design on account of variations in process dynamics as well as interactions between process variables. In this paper, the combination of neural network and dynamic inversion control is applied in Coupled Tank System (CTS) tracking water level problem. The liquids need to be pumped in total process and stored in the two tanks which are coupled together for certain desired level. Transfer function matrix of the system is gained experimentally from the tension loop response of the system. The PID neural network (PID-NN) controller used as a desired system control. Within MATLAB environment, conduction of simulate experiment is to testify the operation of the system according to Settling Time, Rise Time, Steady State Error and Overshoot. Numerical simulations and experiments have both been conducted to prove the validity of the proposed method. It has been attested that capabilities of CTS are ameliorated by suggested proposed method.